2015
DOI: 10.1007/s10980-014-0149-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of impacts of human activities and climate change on water quantity and quality in Finnish agricultural catchments

Abstract: Context We studied the influence of human activities and climate change on water quantity and quality. Human activities included methods of agricultural policy, i.e. land use and management practices. Objectives Finland started to follow EU's agricultural policy in 1995. In this study our main objective was to find out whether the original targets of the Finnish Agri-Environmental Programme (FAEP) were achieved. Methods We analyzed trends in discharge, water quality and climate parameters in 37 years long time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…This study was conducted in the RRV of southern Manitoba (Figure 1). Seven sub-watersheds were selected [6] to span a gradient in nutrient-producing human activities resulting primarily from livestock density and crop cover ( Table 1). A detailed description of the methods of calculation of human activity intensity (livestock and crop) is given by [16].…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…This study was conducted in the RRV of southern Manitoba (Figure 1). Seven sub-watersheds were selected [6] to span a gradient in nutrient-producing human activities resulting primarily from livestock density and crop cover ( Table 1). A detailed description of the methods of calculation of human activity intensity (livestock and crop) is given by [16].…”
Section: Study Areamentioning
confidence: 99%
“…For example, a three-year study of seasonality of nutrient export from 11 Canadian prairie streams showed that total P and total N concentrations and loads both peaked during the snowmelt season [5]. Similarly, in selected Finnish catchments, total P and total suspended solids concentrations tracked changes in seasonal discharge, with highest values in April during snowmelt [6]. This flush of nutrients associated with snowmelt in cold regions is caused by the combined effect of intense runoff (which is dependent upon antecedent moisture conditions such as snow depth as well as the rate of warming [7]), frozen soils which restrict infiltration of snowmelt [7], and the presence of nutrients in the form of residual inorganic fertilizer or organic matter residue (crop, pasture or riparian material; [8]).…”
Section: Introductionmentioning
confidence: 99%
“…The pressures are further exacerbated by the effect of a changing climate, which is predicted to bring more frequent extreme events (Kendon et al, 2014;Murphy et al, 2009), resulting in the likelihood of more winter runoff and longer periods of low flow Wilby et al, 2006), although still with much uncertainty (Arnell, 2011;Kay and Jones, 2012;Prudhomme et al, 2012). In conjunction with projected climatic changes, previous studies have indicated likely increases in sediment and nutrient loads (Crossman et al, 2014;El-Khoury et al, 2015;Jeppesen et al, 2009;Jeppesen et al, 2011;Macleod et al, 2012;Rankinen et al, 2015;Whitehead et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the vast freshwater resources, Finland is already facing the challenge of eutrophication in the rivers and lakes that are close to agricultural production, in particular through nitrogen and phosphorus loadings [85,86]. In addition, the entire Baltic Sea is already affected by eutrophication, due to the intensive use of the sea itself and anthropogenic activities [87,88].…”
Section: Limitations Of the Study And Future Directionsmentioning
confidence: 99%